FINANCIAL LITERACY, INFORMALITY, AND SMALL BUSINESS OPERATIONAL PERFORMANCE IN ZIMBABWE - Taruvinga, Rutendo; Sakarombe, Upenyu (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2024)
Introduction: The exponential growth of small and medium enterprises (SMEs) in many developing economies is a well-documented phenomenon in business literature. However, research indicates that the expansion of most SMEs is hindered by financial illiteracy and high levels of informality, posing significant challenges to their performance and long-term sustainability. Concerns arise from the fact that only a small fraction of these enterprises successfully transition into larger firms. This study sought to address these issues by investigating the levels of financial literacy among 120 SMEs operating in Harare and Bindura, taking into account the pervasive informality within the sector. The research also aimed to evaluate the relationship between financial literacy and SME operational performance. Methods: Employing a quantitative approach within an explanatory research design, data collection was facilitated through a structured questionnaire. To capture the diverse landscape of SMEs operating in an informal context, both purposive and convenience sampling methods were utilized to select participants for the survey. Descriptive and inferential analyses were conducted using SPSS software. Results: The findings of the study revealed a significant positive impact of financial literacy on SME operational performance, indicating that advanced financial literacy can contribute to enhanced business outcomes. Moreover, the research observed an improvement in financial literacy within SME operations, evidenced by increased awareness and application of financial management skills. Conclusion and suggestion: The study recommends that efforts to promote financial literacy among SMEs should be intensified through advanced financial education initiatives, awareness campaigns, and enhanced financial inclusion strategies. Financial service providers are encouraged to play a proactive role in supporting SME growth by investing in financial awareness programs, funding educational initiatives, and actively engaging SMEs in key economic policy frameworks. Ultimately, SMEs are urged to fully embrace financial literacy as a fundamental pathway for achieving sustainable growth and long-term business success amidst the challenges of informality.